2007
DOI: 10.1038/sj.ejcn.1602880
|View full text |Cite
|
Sign up to set email alerts
|

Can dual energy X-ray absorptiometry provide a valid assessment of changes in thigh muscle mass with strength training in older adults?

Abstract: Objective: To determine how dual-energy X-ray absorptiometry (DXA) compares to computed tomography (CT) for measuring changes in total thigh skeletal muscle (SM) mass with strength training (ST) in older adults. Subjects: Fifty previously sedentary, relatively healthy older men (n ¼ 23, 60 (s.d. ¼ 7.5) years) and women (n ¼ 27, 60 (s.d. ¼ 9.3) years). Results: Results indicate that there was a significant increase in thigh SM mass with ST measured by both CT (3.970.4%) and DXA (2.970.6%) methods (both Po0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 30 publications
4
57
2
3
Order By: Relevance
“…This is in contrast to the study by Park et al, who observed a small but significant difference in intrinsic muscle strength in a large group of older type 2 diabetic patients using dual-energy x-ray absorptiometry (DEXA) to evaluate muscle mass [40]. Overestimation of muscle mass by DEXA could account for the lower muscle quality observed [41], as could increased fat infiltration of the muscle, which is found more frequently in type 2 diabetic patients [42]. Analysis of magnetic resonance images allows exclusion of fat and fibrous tissue within muscle compartments.…”
Section: Discussioncontrasting
confidence: 55%
“…This is in contrast to the study by Park et al, who observed a small but significant difference in intrinsic muscle strength in a large group of older type 2 diabetic patients using dual-energy x-ray absorptiometry (DEXA) to evaluate muscle mass [40]. Overestimation of muscle mass by DEXA could account for the lower muscle quality observed [41], as could increased fat infiltration of the muscle, which is found more frequently in type 2 diabetic patients [42]. Analysis of magnetic resonance images allows exclusion of fat and fibrous tissue within muscle compartments.…”
Section: Discussioncontrasting
confidence: 55%
“…1A), as might be expected with long-standing muscle disuse. As an aside, discordant findings between DEXA and CT imaging may relate to limitations of DEXA to discriminate these differences in older adults (15,39). Whole muscle CSA deficits (Ϫ19%) were paralleled by reductions in fiber CSA, which were evident in the three most prevalent fiber types examined (I, IIA, and IIAX).…”
Section: Discussionmentioning
confidence: 99%
“…However, measurements at the whole muscle level may not adequately reflect adaptations in muscle size and structure at the cellular, subcellular, and molecular levels (15,25,39). Because skeletal muscle size and structure at these more basic anatomic levels are well-known regulators of function, characterization of muscle morphology with aging and disease at the cellular and subcellular levels may provide greater insight into functional phenotypes than assessments at the whole tissue level.…”
mentioning
confidence: 99%
“…This hypoxemia is due to the complex interactions between the very high cardiac outputs detailed above, flow limitation at very high minute ventilations, ventilation perfusion matching, pulmonary diffusing capacity, and physiological shunts through the lung. The predominant mechanism or mechanisms accounting for this desaturation is a matter of ongoing debate in the pulmonary and exercise physiology communities (3,118,122,198,219,233,353,366,367). It is also important for the nonexpert to recognize that in male endurance elite athletes, minute ventilations in excess of 150 l/min are frequently seen (8,493).…”
Section: What Are the Effects Of Endurance Training?mentioning
confidence: 99%